Design of a Research Project Focused on the Needs of Influencer Marketing Specialists - Havrylova, Yuliia; Karlíček, Miroslav, 1979-; Tahal, Radek, 1970-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates how Czech influencer marketing specialists use and value data in their work. The research set five goals: to map specific data needs of Czech influencer marketing specialists, to identify the data sources they rely on, to uncover gaps between available information and these needs, to evaluate how well the existing Influmonitor report meets those needs, and to design a research project that fills the remaining gaps. Using semi-structured interviews with thirteen practitioners and thematic analysis, the study revealed interesting insights. Influencer marketing specialists need data on detailed influencer’s audience demographics (age, location, buying habits), credibility of audience (real followers versus bots), engagement rate, trust and sentiment, emotional and content drivers, optimal posting times, platform algorithm updates, rising stars, trends, pricing, ROI benchmarks, influencer performance history, and competitor intelligence. They gather data from many sources–platform dashboards (Instagram Insights, TikTok Analytics), third-party tools (HypeAuditor, Storyclash), in-house sales figures, and informal channels such as newsletters, blogs, LinkedIn and Facebook groups, and peer-shared reports–but this information is often scattered and hard to combine. Major gaps include a lack of Czech-specific audience studies, low transparency on influencer fees, missing trends and information on “rising stars”, and limited metrics on long-term impact of collaboration with influencer and community sentiment.
Influmonitor is a report about how Czech Gen Z perceives influencers; it was appreciated by interviewees for its high-level view of influencer popularity across categories and platforms, influencer–category links, platform associations, spontaneous recall scores, and fatigue indicators; it could be improved by covering a wider range of influencers, explaining why people follow certain creators, adding trustworthiness measures, expanding age segmentation, spotting rising stars, and mapping brand associations with influencers. Building on these insights, two practical solutions were proposed – a bi-weekly Czech influencer marketing newsletter and a structured survey of local audience behavior.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses